2014
DOI: 10.1177/0963662514522169
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between scientific knowledge and fortune-telling

Abstract: This study takes on a relational and situated perspective to understand the relationship between scientific knowledge and fortune-telling. Measures included socio-demographic characteristics, knowledge of scientific facts and methods, and fortune-telling beliefs and practices. A sample of 1863 adults was drawn from a population of Taiwanese citizens using the method of probability proportional to size. The findings showed that knowledge of scientific methods was negatively associated with fortune-telling belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Sociological research in the American population offers findings that people under the age of 35 are more subject to conspiracy beliefs than the elderly (Stempel el al., 2007), as confirmed by research findings by . The results of other studies have shown that younger individuals are more subject to pseudoscientific (Tsai et al, 2012) and paranormal beliefs (predicting the future) (Shein et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Sociological research in the American population offers findings that people under the age of 35 are more subject to conspiracy beliefs than the elderly (Stempel el al., 2007), as confirmed by research findings by . The results of other studies have shown that younger individuals are more subject to pseudoscientific (Tsai et al, 2012) and paranormal beliefs (predicting the future) (Shein et al, 2014).…”
Section: Introductionmentioning
confidence: 92%
“…This has left little space to think through how publics envisage the concept of science itself and integrate it into their worldviews. While researchers pay more attention to the psycho-social factors that cause science scepticism (Baker, 2013; Evans, 2011; Hill, 2014b; Shein et al., 2014), publics’ imagining of science remains, by and large, outside the field’s sphere of interest, especially cases where publics identify with an imagined vision of science.…”
Section: Science Identificationmentioning
confidence: 99%
“…Analogous to research on multilingualism, research into cognitive polyphasia needs to explore the varieties of co-existence between different forms of knowing in everyday life. In many societies, cognitive polyphasia – the diversity of forms of thought – is the rule, not the exception (Jovchelovitch, 2008), and indeed Shein et al (2014) found the co-existence of high scientific enculturation and pseudo-scientific beliefs and fortune-telling practices in Taiwan, in particular among the educated younger generation.…”
Section: The Transformation Of the Unfamiliarmentioning
confidence: 99%